Assessing Seventh-Grade Students’ Critical Thinking Skills on Temperature and Heat Using a Two-Tier Diagnostic Test - Raden Hanna Rifani; Ida Kaniawati; Winny Liliawati (Berkala Ilmiah Pendidikan Fisika, 2026)
Critical thinking is a fundamental competency emphasized within the Merdeka Curriculum, vital for enabling students to analyze scientific phenomena and construct reasoned explanations. This study aimed to diagnose the critical thinking skills of seventh-grade junior high school students regarding temperature and heat material using a two-tier diagnostic test. Employing a descriptive survey method, the research involved 88 students from a public junior high school in Cianjur. An instrument comprising 18 two-tier test items was developed based on Facione’s critical thinking indicators: interpretation, analysis, evaluation, inference, explanation, and self-regulation. The results indicated varied competency levels across the indicators. Students demonstrated moderate performance in interpretation (53.0), analysis (51.5), and evaluation (54.5). In contrast, considerably lower scores were observed in inference (41.3), explanation (38.6), and particularly self-regulation (26.5), revealing significant challenges in drawing logical conclusions, providing coherent scientific justifications, and monitoring their own reasoning processes. These findings align with existing literature indicating that higher-order thinking skills develop gradually and require explicit instructional support. The study confirms the effectiveness of the two-tier test as a diagnostic tool for uncovering both conceptual understanding and cognitive reasoning patterns, providing an empirical profile to guide the design of differentiated, inquiry-based learning strategies in line with the formative assessment goals of the Merdeka Curriculum.